On d-Unit Graphs in Rn - Canoy, Sergio Jr. (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
In this paper, the unit dimension of a graph with respect to a metric d on the space Rn is defined. This generalizes the concept of the Euclidean unit dimension of a graph in the space Rn as defined by various authors in [1], [2], [3], and [4]. It is also shown that two equivalent metrics in Rn may yield different unit dimensions of some complete graphs.